2000
DOI: 10.1093/brain/123.7.1459
|View full text |Cite
|
Sign up to set email alerts
|

Coherence between cerebellar thalamus, cortex and muscle in man: Cerebellar thalamus interactions

Abstract: Local field potentials (LFPs) were recorded in seven unanaesthetized patients between the four adjacent contacts of a macroelectrode stereotactically implanted for the treatment of tremor. The LFPs were presumed to arise predominantly from the nucleus ventralis intermedius (Vim) of the thalamus, the implantation target. They were recorded simultaneously with the ipsilateral EEG and contralateral EMG during an isometric contraction or at rest. The patients had a history of either isolated tremor (essential trem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(114 citation statements)
references
References 46 publications
6
106
1
1
Order By: Relevance
“…The magnitude of ␤ coherence, however, was below 16% and thereby much lower than in the theta band. Values of similar magnitude were reported for ␤ coherence between scalp EEG and recording sites in the cerebellar thalamus (Marsden et al, 2000;Paradiso et al, 2004) and basal ganglia (Marsden et al, 2001;Williams et al, 2002;Fogelson et al, 2006), indicating that activity at these sites also interacts with cortical activity. Anatomically and functionally, the main output of the basal ganglia occurs via the pallidothalamic and nigrothalamic tract to the thalamus.…”
Section: Thalamocortical Interplaysupporting
confidence: 70%
See 1 more Smart Citation
“…The magnitude of ␤ coherence, however, was below 16% and thereby much lower than in the theta band. Values of similar magnitude were reported for ␤ coherence between scalp EEG and recording sites in the cerebellar thalamus (Marsden et al, 2000;Paradiso et al, 2004) and basal ganglia (Marsden et al, 2001;Williams et al, 2002;Fogelson et al, 2006), indicating that activity at these sites also interacts with cortical activity. Anatomically and functionally, the main output of the basal ganglia occurs via the pallidothalamic and nigrothalamic tract to the thalamus.…”
Section: Thalamocortical Interplaysupporting
confidence: 70%
“…LFP recordings come mainly from sites in the cerebellar thalamus (Marsden et al, 2000;Paradiso et al, 2004) or in the basal ganglia (Marsden et al, 2001;Williams et al, 2002;Fogelson et al, 2006) and reflect the sites of surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…However, the present results showed that the discharge rates, bursting, and oscillatory activity in Vim in SCA were not different from those in ET, suggesting that ataxia may occur independent of changes in rate, burst, or oscillatory activity in Vim. The present results are in contrast to the disrupting patterns of background neural activity underlying akinesia/bradykinesia of Parkinson's disease 45, 46. Coherent oscillation underlies movement‐related activities within the motor system including the basal ganglia and cerebellar systems in the normal condition 47.…”
Section: Discussioncontrasting
confidence: 72%
“…Complete identification of the source of the coherence would require simultaneous recordings from the cortex, brain stem, spinal cord, and muscle during the movement. Direct recordings from motor cortex and muscle have been analyzed in the monkey (Jackson et al 2002) and in patients (Marsden et al 2000) and have provided further evidence for the cortical origin of the higher-frequency coherence at least to hand and upper limb muscles.…”
Section: Coherence In Noninjured Controlsmentioning
confidence: 99%